Values Exchange: Using Online Technology to Raise Awareness of Values and Ethics in Radiography Education - Mc Inerney, J; Lees, A (John Wiley & Sons, 2018)
Introduction: Ethics and values are increasingly significant aspects of patientcentred healthcare. While it is widely agreed that ethics and values are essential for healthcare delivery, there is also an acknowledgement that these are areas that are challenging to teach. The purpose of this study is to report a smallscale evaluative research project of a web-based technology with the educational potential to facilitate learning in relation to ethics, values, self-reflection and peer-based learning. Methods: Five diagnostic radiography students took part in a semi-structured focus group with the aim of exploring their experiences of using Values Exchange, an online ethical decision-making framework, to examine practice-based ethical issues. Transcripts were interrogated for key themes. Results: From the thematic analysis three major themes emerged, understanding and appreciating others, addressing the theory-practice gap and delivering a safe and effective learning environment. Perceived limitations of the platform included students’ fear of misinterpreted responses and possibility of poor group dynamics. Conclusions: There are varied approaches to how ethics and values are taught and assessed within health-related environments. Values Exchange is one such teaching tool and has been investigated and described positively by radiography students in this study. Online teaching tools can have a positive effect in helping students identify their own values but require skilled implementation to reap positive rewards.
Keywords: Clinical-decision making; Educational technology; Ethical-decision making; Professional practice; Student